Edukasi Pengelolaan Sampah Berbasis Rumah Tangga - Gunawan, Gunawan; Arsi, Antari Ayuning; Iswari, Rini; Nastiti, Tur (Universitas Negeri Semarang, 2025)
One of the ways that can be done to reduce the amount of waste is by managing waste from the household level as its source. The 3R system (Reduce, Reuse, Recycle), which has been advocated by various groups, has not shown significant results, thus it requires concrete efforts so that it is not just a slogan. Households are the initial key to waste management considering that households are the largest producers of waste. By looking at these conditions, household-based waste management education is one of the important ways to overcome the waste problem.This community service activity aims to increase public awareness and knowledge of household waste management. The method applied in this community service program is through organizing participatory workshops with the community. activities starting from the assessment stage, awareness of problems, practice, and management planning. With this activity comes awareness to encourage changes at the practical level in the community in implementing the 3R.